2015
DOI: 10.1177/0040517515580510
|View full text |Cite
|
Sign up to set email alerts
|

Specifying and testing idealized bust surrogates for testing of female stab-resistant body armor

Abstract: Manufacturers of stab-resistant body armor continually strive to improve the comfort of the armor wearer and maximize protection. As female officers make up a larger portion of the law enforcement and corrections workplace, armor manufacturers have begun to offer designs that accommodate contoured body shapes, such as the female bust region, which results in non-planar armor. Conventional test methodologies for body armor were designed for armor to be tested flat and do not accommodate contoured armor. This wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…These three levels were derived from a PSDB program (1997)(1998)(1999), where a male population was used for stab tests using several different stabbing techniques. 24 It was found that the frequency distribution of the energy delivered by this population could be characterized three levels. Level 1 was the lowest energy threat, level 2 represented medium energy threats and level 3 the highest energy threats.…”
Section: Dynamic Methodsmentioning
confidence: 96%
“…These three levels were derived from a PSDB program (1997)(1998)(1999), where a male population was used for stab tests using several different stabbing techniques. 24 It was found that the frequency distribution of the energy delivered by this population could be characterized three levels. Level 1 was the lowest energy threat, level 2 represented medium energy threats and level 3 the highest energy threats.…”
Section: Dynamic Methodsmentioning
confidence: 96%